Daphnia hybridization along ecological gradients in pelagic environments: the potential for the presence of hybrid zones in plankton - Petrusek, Adam; Seda, Jaromir; Machácek, Jiri; Ruthova, Stepánka; Smilauer, Petr (Philosophical transactions of the Royal Society of London. Series B, Biological sciences, 2008)
The relative homogeneity of pelagic environments has been regarded as the reason for the absence of hybrid zones for hybridizing planktonic Daphnia (Crustacea: Cladocera); occasional dominance of interspecific hybrids over parental species was explained by their temporal superiority in fluctuating environments. However, water bodies with spatially varying environmental conditions might facilitate the formation of hybrid zones in plankton. We studied the distribution of species and hybrids of the Daphnia longispina complex in 11 canyon-shaped reservoirs, localities characterized by horizontal environmental gradients (particularly of food supply and size-selective predation); we also analysed patterns of carapace size and fecundity among coexisting taxa. Spatial distribution of taxa agreed with their ecological characteristics; those showing different affinities along longitudinal reservoir profiles differed in size according to the presumed fish predation gradient. Only hybrids of Daphnia galeata with Daphnia cucullata and D. longispina (=hyalina) were recorded. The latter two species preferred opposite ends of gradients, such spatial segregation probably explaining the absence of their hybrids. Distributional patterns were relatively stable in two consecutive summers, apart from a substantial decline of D. galeata X cucullata in the second year. The observed pattern of a hybrid-dominated zone in intermediate conditions suggests that local Daphnia hybrid zones may indeed form within reservoirs.
Keywords: demografie; hybridizace genetická; DNA, Ribosomal Spacer; Time Factors; Isoenzymes; Daphnia; zvířata; ekosystém; Demography; Ecosystem; Zooplankton; izoenzymy; Hybridization, Genetic; mezerníky ribozomální DNA; zooplankton; časové faktory; Animals